A New Rrivalry between Great Britain and France over the Middle East and The Mediterranean Sea during the First World War - Farajat, Mazen Mohammad; AlFarajat, Rabie Khaled (Dirasat: Human and Social Sciences, 2025)
Objectives: This study aimed at highlighting the new rivalry between Great Britain and France over the middle east and the Mediterranean Sea between 1912 and 1916. Method: The researchers used the quantitative method; mainly the inductive-deductive method for analyzing the events in historical texts in the years under study. Results: The study results showed that English ambitions were confronted with a united reaction by the French government and the emerging colonial entities. They also showed that the French policy adopted a number of political, diplomatic and military strategies which did not succeed because of the countermeasures that were taken by Great Britain. Conclusions: The study asserts the notion that the Middle East and the Mediterranean Sea have gained strategic importance in international politics due to the region’s unique geographical location since it links three continents, namely, Asia, Africa and Europe together and it is considered an area where the political and economic interests of many European countries intersect, especially after the decline of the Ottoman Empire. Despite the short-lived military French campaign in Egypt, this campaign is considered one of the most influential events in the history of Middle East and the Mediterranean Sea.